Propagation of back‐arc extension into the arc lithosphere in the southern New Hebrides volcanic arc. (24th September 2015) - Patriat, M.; Collot, J.; Danyushevsky, L.; Fabre, M.; Meffre, S.; Falloon, T.; Rouillard, P.; Pelletier, B.; Roach, M.; Fournier, M.
Abstract New geophysical data acquired during three expeditions of the R/V Southern Surveyor in the southern part of the North Fiji Basin allow us to characterize the deformation of the upper plate at the southern termination of the New Hebrides subduction zone, where it bends eastward along the Hunter Ridge. Unlike the northern end of the Tonga subduction zone, on the other side of the North Fiji Basin, the 90° bend does not correspond to the transition from a subduction zone to a transform fault, but it is due to the progressive retreat of the New Hebrides trench. The subduction trench retreat is accommodated in the upper plate by the migration toward the southwest of the New Hebrides arc and toward the south of the Hunter Ridge, so that the direction of convergence remains everywhere orthogonal to the trench. In the back‐arc domain, the active deformation is characterized by propagation of the back‐arc spreading ridge into the Hunter volcanic arc. The N‐S spreading axis propagates southward and penetrates in the arc, where it connects to a sinistral strike‐slip zone via an oblique rift. The collision of the Loyalty Ridge with the New Hebrides arc, less than two million years ago, likely initiated this deformation pattern and the fragmentation of the upper plate. In this particular geodynamic setting, with an oceanic lithosphere subducting beneath a highly sheared volcanic arc, a wide range of primitive subduction‐related magmas has been produced including adakites, island arc tholeiites, back‐arc basin basalts, and medium‐K subduction‐related lavas.